Designing a Web-Based Online Sales System for The Krakatau Inderapura Minimarket - Ramadhan, Fandy; Syahputra, Dinur (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
The use of information technology in the business world is growing rapidly, including in online sales systems. Krakatau Inderapura Minimarket, as a micro-business engaged in the sale of various daily necessities in the Inderapura area, recognizes the need to adapt technology to expand its market reach and improve customer service. This study aims to design and develop a web-based online sales system that allows customers to make purchases easily and efficiently. The system development method used is the waterfall method with stages of requirements analysis, system design, implementation, testing, and maintenance. This system is designed to allow customers to view a list of available products, place orders online, select payment methods, and track order status in real-time. In addition, the system also provides administrative features for minimarket managers to manage inventory, view sales reports, and manage store profiles. The results of this study show that the implementation of a web-based online sales system at Minimarket Krakatau Inderapura can increase ease of access for customers when shopping, improve the operational efficiency of minimarkets, and provide a better overall shopping experience for customers.